Strength performance parameters and muscle activation adopting two antagonist stretching methods before and between sets - Paz, G.; Maia, M.; Whinchester, J.; Miranda, H. (Science & Sports, 2016)
Objectives: The purpose of this study was to investigate the acute effects of passive static stretching and proprioceptive neuromuscular facilitation applied in antagonist muscles (shoulder horizontal adductors) in inter-set rest period on repetition performance and muscle activation.